An integrated qualitative and quantitative study on sexual and reproductive health problems faced by women with disabilities in Chandigarh, India - Ruchi Sharma; Ajit Kumar; Vanita Suri; Sukhpal Kaur; Amar Jeet Singh (Int. J. Gynecol. Obstet., 2023)
ObjectivesTo estimate the prevalence of sexual and reproductive health (SRH) problems among women with disabilities (WWD) in Chandigarh, India, and to ascertain the difficulties experienced by WWD in accessing hospital services. MethodsThis cross-sectional study was conducted during 2014 to 2017 in Chandigarh, India. The study participants were women 15 years and older with at least 40% disability. A pretested questionnaire and in-depth interview were used to determine sociodemographic profile, medical history, sexual and reproductive morbidity, treatment-seeking behavior, and the type, extent, and course of the disability. Verbatim responses of the participants were noted. Data were manually coded and collated into possible themes. ResultsPostpolio residual paralysis (80; 30.7%) was the main reported disability, followed by severe sight impairment (52; 19.9%). A majority (170; 65%) of participants were unmarried. Of them, 66 (39%) were not willing to get married. The prevalence of SRH problems was high (151; 57.9%) among WWD, and only 82 (54%) took treatment. Dysmenorrhea (47; 31.1%), irregular periods (36; 23.8%), and vaginal discharge (17; 11.3%) were the main problems reported. The WWD in this study were likely to hide their SRH problems from others out of shame or fear. ConclusionAmong WWD, the prevalence of SRH problems is high and obtaining relief is difficult.
Keywords: Annoyance; Health impact factors; Questionnaire noise; Traffic noise